Taiwanese parents’ perspectives on young children’s use of information communication technology - Luo, Yi Fang; Yang, Shu Ching; Chou, Kun Yi; Lee, Hsin Tien (Frontiers in Psychology, 2023)
This study surveyed 629 Taiwanese parents to explore their attitudes toward their young children's use of information communication technology (ICT), usage patterns, and the interplay with socioeconomic status. The findings revealed a significant disconnect: although approximately 50% of parents considered above six years old to be a suitable age for children to start ICT, over 80% of children had already engaged with ICT before that age, indicating a large disparity between parental expectations and actual initiation. Furthermore, parents highlighted "learning interest" and "various content" as the most positive impacts of children's ICT use, while "addiction and overreliance" emerged as their primary concern. Notably, parents, as a whole, tended to perceive their child's ICT use more negatively than positively, with fathers displaying greater acceptance of negative viewpoints than mothers. Parental attitudes toward children's ICT use were categorized into five clusters, ranging from balanced and optimistic views to value emphasis, conservatism, and negative doubts. This classification underscores the intricate and multifaceted nature of parental perspectives, encompassing both positive and negative outlooks on children's ICT utilization. The findings underscore the nuanced character of parents' attitudes toward technology, shaped by the intricacies and challenges posed by the digital era. These insights emphasize that parental attitudes go beyond a simplistic positive-negative divide, reflecting a comprehensive response to the opportunities and complexities inherent in the digital age.